Coverage reflects importance of fishing to community. (December 2015) - Evans, Suzannah; Riffe, Daniel
This study compares the coverage of new federal regulations on New England fisheries in local newspapers in historic fishing towns and that in regional newspapers. Local newspapers were much more likely to present anti-regulatory viewpoints and name one person or entity as a villain, thereby dismissing or demeaning pro-regulation environmental activists or government officials.